ANALISIS HUKUM EKONOMI SYARIAH TERHADAP DISTRIBUSI MINUMAN PRE-WORKOUT TANPA LABEL HALAL DI KOMUNITAS FITNESS - Mutiya, Putri; Huda, Rahmatul; Hani, Umi (Media Mahardhika, 2026)
The fitness industry has experienced rapid growth alongside the increasing public awareness of the importance of a healthy lifestyle. One of the most popular products among fitness communities is pre-workout beverages, which are claimed to enhance energy and performance during exercise. However, the distribution of these products generally lacks halal certification, raising concerns among Muslim consumers regarding the permissibility of their consumption. Based on this issue, this study addresses two main research questions: (1) How are non-halal-certified pre-workout beverages distributed within fitness communities? and (2) How does Islamic Economic Law analyze the distribution of pre-workout beverages without halal certification? The purpose of this study is to examine the distribution practices of non-halal-certified pre-workout beverages within fitness communities and to analyze the provisions of Islamic Economic Law related to the distribution of products without halal labels. This research employs a qualitative method through interviews and literature review. The findings reveal that non-halal certified pre-workout products are widely distributed through both physical stores and online marketplaces. Most of these products are imported, featuring English language labels and lacking halal certification from the Indonesian Ulema Council (MUI). Additionally, the study found low awareness among both Muslim consumers and business actors regarding the importance of halal certification. From the perspective of Islamic Economic Law, such distribution practices potentially violate the principles of halal and thayyib. Therefore, this study recommends the need for increased education, stricter regulations, and active involvement of halal certification bodies to ensure consumer protection in the fitness sector.